State Anxiety Impairs Attentional Control When Other Sources of Control Are Minimal - Booth, Robert William; Peker, Müjde (Taylor & Francis, 2016)
Research suggests anxiety impairs attentional control; however, this effect has been unreliable. We argue that anxiety’s impairment of attentional control is subtle, and can be obscured by other non-emotional sources of control. We demonstrate this by examining conflict adaptation, an enhancement in attentional control following a trial with high conflict between distracter and target stimuli. Participants completed a Stroop task featuring incongruent (e.g. RED in green font; high-conflict) and control (e.g. +++ in green font; low-conflict) trials. More state-anxious participants showed greater Stroop interference following control trials, but interference was uniformly low following incongruent trials. This suggests state anxiety can impair attention, but other sources of top-down control – such as conflict adaptation – can easily overcome this impairment. This is consistent with recent theories of anxious cognition and shows that anxiety researchers must attend to the dynamics and sources of attentional control.
Booth, Robert W. (MEF Author) -- 13.Eylül.2017 tarihine kadar yazar sürümüne erişim kısıtı vardır.
Keywords: Stroop; Attentional control; Anxiety; Reactive control; Conflict-adaptation; Conflict Adaptation